PENGGUNAAN MEDIA IT DALAM PEMBELAJARAN - Rioga Fransistyawan; Nur Kholifatul Ummah; Vina Syayidatul Fitriya; Jihan In Fatiha (STKIP Subang, 2025)
The advancement of Science and Technology provides technological advancesthat enable humans to obtain sophisticated facilities. Various facts inmodernization, every day are provided by families, communities and also the worldof information. The rise of the advertising world forces information to circulatemore easily, able to stimulate curiosity, a desire to try as a result of publicationsthat are neatly designed by communication experts at high costs with widespreadand profound impacts. Information comes faster than our breakfast, is eaten fasterthan parental advice. The information enters through ICT (informationcommunication technology) windows. The success of learning activities in a schoolis influenced by various factors, namely, teacher factors, students, curriculum,social environment and so on. Teachers are an important factor in the learningprocess with the main task of helping students to be able to learn according totheir needs and interests. The use of this media is expected to improve studentlearning outcomes.